2023
DOI: 10.1029/2023jc019687
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Arctic Ocean Sea Ice Export Between Nares Strait and the Canadian Arctic Archipelago

Abstract: The recent decline in the Arctic Ocean sea ice extent during the summer months (e.g., Parkinson & DiGirolamo, 2021) is one of the most visible features of a warmer Arctic. However, identifying the processes responsible for the Arctic's sea ice decline is challenging because ice is very dynamic and does not always melt locally. While a considerable amount of sea ice does melt locally in the Arctic Ocean (Babb et al., 2022;Kwok & Cunningham, 2010;Perovich et al., 2008), a large amount is also transported out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Ice export through these channels is limited by the seasonal formation of ice arches (also known as ice bridges or barriers; Hibler et al, 2006;Kirillov et al, 2021;Melling, 2002) that impede ice motion, yet as the Arctic warms these arches are forming for shorter periods and occasionally not forming at all, allowing increased ice export (Howell et al, 2023;Howell & Brady, 2019;. Annual ice export into Nares Strait increased from 33,000 km 2 between 1996 and 2002 (Kwok, 2005) to 87,000 km 2 between 2019 and 2021 and more recently 95,000 km 2 between 2017 and 2021 (Howell et al, 2023). Meanwhile, annual ice export into the QEI increased from 8,000 km 2 between 1997 and 2002 (Kwok, 2006) to 25,000 km 2 between 1997 and 2018 (Howell & Brady, 2019), with a recent peak of 120,000 km 2 in 2020 (Howell et al, 2023).…”
Section: Myi Exportmentioning
confidence: 99%
See 4 more Smart Citations
“…Ice export through these channels is limited by the seasonal formation of ice arches (also known as ice bridges or barriers; Hibler et al, 2006;Kirillov et al, 2021;Melling, 2002) that impede ice motion, yet as the Arctic warms these arches are forming for shorter periods and occasionally not forming at all, allowing increased ice export (Howell et al, 2023;Howell & Brady, 2019;. Annual ice export into Nares Strait increased from 33,000 km 2 between 1996 and 2002 (Kwok, 2005) to 87,000 km 2 between 2019 and 2021 and more recently 95,000 km 2 between 2017 and 2021 (Howell et al, 2023). Meanwhile, annual ice export into the QEI increased from 8,000 km 2 between 1997 and 2002 (Kwok, 2006) to 25,000 km 2 between 1997 and 2018 (Howell & Brady, 2019), with a recent peak of 120,000 km 2 in 2020 (Howell et al, 2023).…”
Section: Myi Exportmentioning
confidence: 99%
“…For large channels like Fram Strait, and channels into the Kara and Barents Seas, F was calculated weekly using fields of sea ice drift and concentration from the NSIDC data sets Total ice export into the QEI has been quantified for the period from 1997 to 2002 (Kwok, 2006), 1997-2018(Howell & Brady, 2019, and more recently 2017-2021 (Howell et al, 2023). MYI flux was also determined during the latter period and revealed that MYI comprises 85% of the total ice flux into the QEI.…”
Section: Myi Budgetmentioning
confidence: 99%
See 3 more Smart Citations